2012
DOI: 10.4274/jcrpe.751
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Efficacy of Insulin Pump Therapy in Children with Type 1 Diabetes Mellitus

Abstract: Objective: Insulin pumps have been well established for insulin delivery. However, questions about long-term efficacy of insulin pump therapy still remain. We evaluated the long-term efficacy of continuous insulin infusion pump therapy (CSII) in pediatric patients with type 1 diabetes mellitus (T1DM).Methods: This was a retrospective observational study which included 131 patients with T1DM who transitioned to an insulin pump from multiple daily insulin (MDI) injections between 1999 and 2009 and were followed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 21 publications
1
7
0
3
Order By: Relevance
“…Some studies have shown that the HbA1c level is not related to the number of insulin injections [13]. We believe that the results of our study are in agreement with the finding that compliance with and desire for better glycemic control are more important than the insulin delivery method [14], as they strengthen patients' self-management abilities. Because our study was retrospective and no information about diet and exercise was available for our outpatients, we could not evaluate their comprehensive management abilities.…”
Section: Discussionsupporting
confidence: 91%
“…Some studies have shown that the HbA1c level is not related to the number of insulin injections [13]. We believe that the results of our study are in agreement with the finding that compliance with and desire for better glycemic control are more important than the insulin delivery method [14], as they strengthen patients' self-management abilities. Because our study was retrospective and no information about diet and exercise was available for our outpatients, we could not evaluate their comprehensive management abilities.…”
Section: Discussionsupporting
confidence: 91%
“…Plotnick et al 7 found only transient improvement in HbA1c at 3-6 months after pump therapy. Batajoo et al 8 found no difference in glycemic control in patients on insulin pump therapy compared with MDI at 30 months of follow-up. In contrast, Nimri et al 9 reported longterm improvement in children with type 1 diabetes after initiation of insulin pump therapy, as did Weinzimer et al 10 Only three studies have examined the long-term efficacy of insulin pumps in adults.…”
Section: Discussionmentioning
confidence: 98%
“…The strength of this study is that although it is not a RCT, it analyses “real‐world” outcomes of a large population‐based cohort over a longer duration than previously reported. It differs from other pediatric studies which often include only a small number of patients, have a much shorter follow‐up time, and do not include a control group (patients on injection therapy) . Furthermore, data in this study come from a population‐based database with high case ascertainment, and pairs were matched with a random‐sampling algorithm that minimizes a potential selection bias.…”
Section: Discussionmentioning
confidence: 99%
“…It differs from other pediatric studies which often include only a small number of patients, have a much shorter follow-up time, and do not include a control group (patients on injection therapy). [6][7][8][9][10] Furthermore, data in this study come from a population-based database with high case ascertainment, and pairs were matched with a random-sampling algorithm that minimizes a potential selection bias. There are few pediatric randomized controlled trials comparing patients on pump therapy and patients on injection therapy, and all have a duration of less than 1 year.…”
Section: Severe Hypoglycemia and Dkamentioning
confidence: 99%